First ray mobility and posterior tibial tendon dysfunction (PTTD) in persons with flatfoot: A case control study. (December 2018) - Heng, Marabelle L.; Krishnasamy, Priathashini; Kong, Pui W.
Highlights: What is already known? Tibialis posterior tendon condition may be associated with first ray mobility. Posterior tibial tendon dysfunction (PTTD) commonly presents with flat feet. Flat-footed individuals can be asymptomatic and do not experience any symptoms of PTTD. What this study adds? Maximum dorsal displacement of the first ray did not differ between PTTD patients and asymptomatic flat-footed controls. Clinical evaluation of first ray stiffness did not differ between PTTD patients and controls. First ray mobility was not associated with PTTD in flat-footed persons. Abstract: Background: While posterior tibial tendon dysfunction (PTTD) commonly presents with flat feet and has been thought to be associated with first ray mobility, many flat-footed individuals are asymptomatic and do not experience any symptoms of PTTD. Thus, there is a need to control for foot type when studying factors related to PTTD. This study aimed to clarify if first ray mobility differed between flat-footed individuals with and without symptoms of PTTD. It was hypothesized that PTTD patients would display higher mobility of the first ray than asymptomatic flat-footed controls. Methods: Given that PTTD patients were often flat-footed, asymptomatic flat-footed individuals were chosen as controls to remove flatfoot as a potential confounding factor. We recruited 32 flat-footed subjects, of which 16 exhibiting PTTD symptoms and 16 asymptomatic controls matched for age, sex and body mass index. First ray mobility was assessed using subjective classification ("stiff", "normal" or "hypermobile") and maximum dorsal displacement using a ruler indicator. Mann-Whitney U was used to test for between-groups differences. Results: Subjective classification was similar between PTTD and control groups (both groups: 38% "normal" joint mobility). No significant differences were found between PTTD patients and asymptomatic controls in first ray displacement [median (IQR), PTTD: 6.00 (1.75) mm; control: 6.00 (1.00) mm; P = .31]. Conclusions: First ray mobility was not associated with PTTD in flat-footed persons. When evaluating symptoms of PTTD, clinicians should pay attention to factors other than first ray mobility.